Exploring The Development Of Human Capital For Desapreneur Development In Malaysia - Nurul Nadiah Ahmad; Wan Mohammad Taufik Wan Abdullah; Nurul Nazlia Jamil (Human Resource Management Academic Research Society, 2024)
Indexed by ERA